2006
DOI: 10.1111/j.1467-8624.2006.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Trajectories of Ethnic Identity Among Urban Black and Latino Adolescents

Abstract: The current study modeled developmental trajectories of ethnic identity exploration and affirmation and belonging from middle to late adolescence (ages 15-18) and examined how these trajectories varied according to ethnicity, gender, immigrant status, and perceived level of discrimination. The sample consisted of 135 urban low-income Black and Latino adolescents (42% male, 34% Black, 66% Latino). Consistent with developmental theory, individual growth modeling identified an average quadratic trajectory of ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

37
303
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(344 citation statements)
references
References 56 publications
37
303
4
Order By: Relevance
“…Because recent work shows that Latino male adolescents, compared to female adolescents, are given more freedom to explore the world outside of the family context (Raffaelli & Ontai, 2004), it is possible that male adolescents have more experiences with discrimination and, as a result, are more cognizant of the effects of discrimination on their lives. In work with Black adolescents, Pahl and Way (2006) suggested that Black adolescents' continuous exposure to racism may lead to continuous exploration of ethnicity; it is possible that the same reasoning can be applied to the gender difference found in the current study. Because, compared to female adolescents, Latino adolescent male adolescents are more likely to experience discrimination and experience higher levels of discrimination (Lopez, 1995), these elevated rates of discrimination may prompt ethnic identity formation processes more strongly for male adolescents than for female adolescents.…”
Section: Discrimination and Ethnic Identitymentioning
confidence: 87%
See 3 more Smart Citations
“…Because recent work shows that Latino male adolescents, compared to female adolescents, are given more freedom to explore the world outside of the family context (Raffaelli & Ontai, 2004), it is possible that male adolescents have more experiences with discrimination and, as a result, are more cognizant of the effects of discrimination on their lives. In work with Black adolescents, Pahl and Way (2006) suggested that Black adolescents' continuous exposure to racism may lead to continuous exploration of ethnicity; it is possible that the same reasoning can be applied to the gender difference found in the current study. Because, compared to female adolescents, Latino adolescent male adolescents are more likely to experience discrimination and experience higher levels of discrimination (Lopez, 1995), these elevated rates of discrimination may prompt ethnic identity formation processes more strongly for male adolescents than for female adolescents.…”
Section: Discrimination and Ethnic Identitymentioning
confidence: 87%
“…Because existing empirical work with Latino youth (i.e., Puerto Rican, Dominican, Caribbean, Central American, and South American) has established that discrimination is a significant reality for Latino youth (Fisher, Wallace, & Fenton, 2000;Martinez, DeGarmo, & Eddy, 2004;Rosenbloom & Way, 2004), examining its potential influence on ethnic identity formation is critical. To our knowledge, one study that included a subsample of predominately Puerto Rican and Dominican Latino adolescents (i.e., Pahl & Way, 2006) has examined the longitudinal association between perceived discrimination and ethnic identity. Pahl and Way (2006) found that growth in perceived discrimination predicted growth in exploration but not affirmation.…”
Section: Perceived Discriminationmentioning
confidence: 99%
See 2 more Smart Citations
“…It can encompass both sense of identity and social relations and is often measured as how close one feels to, and how much time they prefer to spend with, co-ethnics (Phinney & Ong, 2007). Empirical evidence for the relationship between ethnic identity and U.S. length of stay is scant, but longitudinal studies find that ethnic identity decreases over time for Latinos adolescents (Pahl & Way, 2006). Other work on Mexican families suggests that ethnic identity diminishes across generations (Jiménez & Fitzgerald, 2007).…”
Section: Ethnic Identitymentioning
confidence: 99%